Development of a device and software complex for acoustic diagnostics of processes occurring in the supercritical state of a liquid and monitoring the work of a magnetic drive unit - Boriskin, V.M.; Churikov, V.V.; Momot, V.O. (Problems of Atomic Science and Technology, 2022)
There is a problem of studying the processes that occur during the transition of a liquid to a supercritical state and in the process of studying and conducting experiments. There is also a problem of controlling the operation of the electromagnetic device system. Since mechanical, electronic, and other control methods are complicated by the conditions (extremely high pressure, high temperature, location of a part that needs control inside a sealed metal system and is under radiation), an acoustic research method was chosen. As a result of the development, a device based on STM32F407VGT6, DP83848, MAX9814 was created that allows you to receive acoustic data and transmit them over considerable distances using an Ethernet network. Also, applications were developed that enable visualization, storage and processing of acoustic data: a TCP server for data exchange, an operator application that helps to visually control the operation of the magnetic drive and save acoustic data in CSV format, an application for visualization and processing of stored data using methods of statistical and spectral analysis.